Effectiveness of an Educational Program Directing toward the Domestic Violence Behavior among Secondary School Students - Amena Razzaq Jasim; Arkan Bahlol Naji (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Domestic violence is now considered as a global health issue. It is defined as a threat or physical, psychological and/or emotionally violent act. Methods: An experimental design was used to guide this study. The study was conducted at three secondary schools for girls from Al-Mahmudiya district. The study included a sample of 200) secondary school student girls who were randomly selected. The education program is implemented through three sessions. Each session is scheduled for 45-minutes.Study instrument: A questionnaire was adopted from Elabani (2015). The behaviors considered as domestic violence against women scale was used to measure behaviors that women consider them implying domestic violence against them. The study results revealed that was a (a priori p = 0.01) significant difference in the domestic violence as a behavior over time for participants in the study group. The omnibus effect (measure of association) for this analysis is .883, which indicates that approximately 88% of the total variance in the domestic violence as a behavior values is accounted for by the variance in the administered intervention.Conclusion : The implemented program positively affected the values of the domestic violence as a behavior, for the study group by time compared to the control group.